2021
DOI: 10.3390/nano11020434
|View full text |Cite
|
Sign up to set email alerts
|

Large-Area Nanocrystalline Caesium Lead Chloride Thin Films: A Focus on the Exciton Recombination Dynamics

Abstract: Caesium lead halide perovskites were recently demonstrated to be a relevant class of semiconductors for photonics and optoelectronics. Unlike CsPbBr3 and CsPbI3, the realization of high-quality thin films of CsPbCl3, particularly interesting for highly efficient white LEDs when coupled to converting phosphors, is still a very demanding task. In this work we report the first successful deposition of nanocrystalline CsPbCl3 thin films (70–150 nm) by radio frequency magnetron sputtering on large-area substrates. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
16
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(23 citation statements)
references
References 56 publications
6
16
1
Order By: Relevance
“…The narrow peak 1 is manifest only at low temperatures and its position in energy at 2.97 eV is very close to the low-temperature exciton absorption of CsPbCl 3 . The position of this peak agrees with the published data on photoluminescence of bulk crystals, 19,20,35 microcrystals and films, 36,37 of CsPbCl 3 . It should be noted, however, that in nanocrystals this peak is shifted towards higher energy, 38,39 similar to what is observed in other inorganic halide perovskites.…”
Section: X-ray Luminescencesupporting
confidence: 90%
“…The narrow peak 1 is manifest only at low temperatures and its position in energy at 2.97 eV is very close to the low-temperature exciton absorption of CsPbCl 3 . The position of this peak agrees with the published data on photoluminescence of bulk crystals, 19,20,35 microcrystals and films, 36,37 of CsPbCl 3 . It should be noted, however, that in nanocrystals this peak is shifted towards higher energy, 38,39 similar to what is observed in other inorganic halide perovskites.…”
Section: X-ray Luminescencesupporting
confidence: 90%
“…However, the low-temperature values for the band gap energy below 300 K in ref. [ 27 ] are strongly different with all the rest of published experimental results ([ 12 ] and refs therein). The red shift reported in Figure 6 a–c highlights a change in the band gap energy, which is possibly related to the phase transitions that are reported for CsPbCl 3 in the T range (300–330 K) [ 13 , 14 , 15 , 16 ].…”
Section: Discussioncontrasting
confidence: 79%
“…The dynamic working pressure was 2 × 10 −6 atm and the deposition rate was between 5 and 7 × 10 −2 nms −1 . The samples were fully characterized concerning morphology, structure, and stoichiometry, as extensively described in [ 12 , 18 , 19 ].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Yan et al reported that the grain size of MAPbBr 3 thin film can be modified by changing the molar ratio of the organic to inorganic precursor, and PL emissions can reach their maximum when the molar ratio is two [30]. Falsini et al showed that there are two PL emissions in CsPbCl 3 thin film, and these emissions are attributed to the different morphologies of the crystallites [31].…”
Section: Characterization Of Mapbi 3 Filmsmentioning
confidence: 99%